2016
DOI: 10.1093/jrr/rrw004
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation using robotic image-guided stereotactic radiotherapy of recurrent head and neck cancer

Abstract: The purpose of this study was to examine the prognosis for patients with head and neck cancer after reirradiation using Cyberknife stereotactic body irradiation with special focus on mucosal ulceration. We conducted a retrospective multi-institutional review of 107 patients with previously irradiated head and neck cancer. The median follow-up time for all patients was 15 months, and the 2-year overall survival rate was 35%. Significant prognostic factors for overall survival were primary site (nasopharynx vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…55 Two prospective studies from France have shown support for SBRT reirradiation. Yamazaki et al 55 reported a large multi-institutional review of 107 patients who received SBRT reirradiation utilizing a robotic radiosurgery system to a median dose of 30 Gy in 5 fractions.…”
Section: University Of Pittsburgh Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Two prospective studies from France have shown support for SBRT reirradiation. Yamazaki et al 55 reported a large multi-institutional review of 107 patients who received SBRT reirradiation utilizing a robotic radiosurgery system to a median dose of 30 Gy in 5 fractions.…”
Section: University Of Pittsburgh Seriesmentioning
confidence: 99%
“…Cengiz et al 49 reported on 47 patients receiving a median dose of 30 Gy in 5 daily fractions, and found a particularly high rate of 15% G5 toxicity, and 18% rate of carotid artery rupture. 55 In a Japanese study on 381 patients with SBRT reirradiation, 8.4% developed carotid artery rupture at a median of 5 months after SBRT. 55 The rates of carotid artery rupture after SBRT are much lower in series that used an alternating day treatment regimen.…”
Section: Reirradiation Toxicitymentioning
confidence: 99%
“…However, late toxicity rates could be higher than with conventional fractionation, especially for larger volumes or critical situations like carotid invasion of more than 180 degrees. 31 Regarding the dose to critical structures like brainstem or mandible, the added maxima of the cases shown here clearly exceed the limits previously reported for radiation myelopathy (eg, BED(2) of 135.5 Gy and EQD2 of 67.5 Gy according to Nieder et al 32 ) for the first patient with an EQD2(2) = 67.78 Gy and for osteoradionecrosis of the mandible (e.g., already 6%-15% risk for an EQD2 of 69-81 Gy according to Studer et al 33 ) for the second patient with a maximum dose of 109.26 Gy EQD2 (2). However, these facts have to be interpreted very carefully and cannot lead to safe conclusions.…”
Section: Casementioning
confidence: 99%
“…Acute carotid blowout syndrome is profuse, uncontrollable bleeding . The reported incidence of acute CBOS after reirradiation for recurrent head and neck cancers ranges between 3% and 10% depending on radiotherapy schema, being highest in large fraction size treatments …”
Section: Introductionmentioning
confidence: 99%
“…15 The reported incidence of acute CBOS after reirradiation for recurrent head and neck cancers ranges between 3% and 10% depending on radiotherapy schema, being highest in large fraction size treatments. 16 The purpose of this study is to analyze dose/volume/outcome data from a retrospective clinical trial in order to estimate the values of commonly used NTCP models and their ability to accurately represent the incidence of CBOS; and additionally, to identify dose thresholds that could ensure lower risks of acute CBOS when they are satisfied .…”
Section: Introductionmentioning
confidence: 99%